A Multicenter Phase 1 Study of γ -secretase inhibitor RO4929097 in Combination with Capecitabine in Refractory Solid Tumors - LoConte, Noelle K. (Invest New Drugs, 2014)
BACKGROUND: RO4929097 is an oral inhibitor of γ -secretase that results in Notch signaling inhibition. Prior work has demonstrated that Notch signaling inhibition enhances chemotherapy sensitivity of cancer cells. This phase I study was conducted to determine maximum tolerated dose (MTD), toxicities and efficacy of RO4929097 and capecitabine in advanced solid tumors. METHODS: Patients with refractory solid tumors received capecitabine at a fixed dose of 1000 mg/m(2) twice daily with escalating doses of RO4929097 on a 21-day cycle in a 3+3 design. Capecitabine was administered for 14 days and the RO49029097 once daily, 3 days per week, both for a 21 day cycle.. RESULTS: Thirty patients were treated on six dose levels (20 to 150 mg). The maximally tolerated dose was not reached. One dose limiting toxicity was observed at each level 3 through 6 (hypophosphatemia, fatigue, and nausea/vomiting). Three confirmed partial responses were observed: two patients with fluoropyrimide-refractory colon cancer and one patient with cervical cancer. Autoinduction of RO4929097 was demonstrated with increasing dose levels and duration. CONCLUSIONS: The recommended phase 2 dose is capecitabine 1000 mg/m(2) orally twice daily on days 1 through 14 with RO4929097 20 mg orally once daily on days 1-3, 8-10 and 15-17 with a 21 day cycle. Clinical benefit was observed in cervical and colon cancer. Autoinduction of RO4929097 was seen both with increasing cycle number and increasing dose. Plasma concentrations of RO4929097 were above those needed for Notch inhibition.